2005
DOI: 10.1111/j.1460-9592.2005.01672.x
|View full text |Cite
|
Sign up to set email alerts
|

Cuff filling volumes and pressures in pediatric laryngeal mask airways

Abstract: Since the volume of air which is effectively required depends on several factors and varies between patients, the cuffs should be inflated only with the minimum volume of air required to form an effective seal with the respiratory and gastrointestinal tracts and the cuff pressure should be controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 24 publications
8
41
1
Order By: Relevance
“…Outcomes measured were airway leak pressure, ease and time for insertion, fibreoptic examination, incidence of gastric insufflation and complications. Median (IQR [range]) time to successful device placement was faster with the air-Q SP (12 (10-15 [5][6][7][8][9][10][11][12][13][14][15][16][17][18])) s than with the LMA-Unique (14 (12-17 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]) s; p = 0.05). There were no statistically significant differences between the air-Q SP and LMA-Unique in initial airway leak pressures (16 (14-18 [10- …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes measured were airway leak pressure, ease and time for insertion, fibreoptic examination, incidence of gastric insufflation and complications. Median (IQR [range]) time to successful device placement was faster with the air-Q SP (12 (10-15 [5][6][7][8][9][10][11][12][13][14][15][16][17][18])) s than with the LMA-Unique (14 (12-17 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]) s; p = 0.05). There were no statistically significant differences between the air-Q SP and LMA-Unique in initial airway leak pressures (16 (14-18 [10- …”
Section: Discussionmentioning
confidence: 99%
“…An increase in airway leak pressure of both devices at 10 min may indicate some degree of moulding of the device in the posterior pharynx improving airway seal. Adjustments of the intracuff pressure are sometimes needed to maintain an adequate airway seal and prevent overinflation of the cuff when using supraglottic airways [20][21][22]. In this respect, the use of the air-Q SP may represent a benefit, as it may be more convenient than supraglottic airways with inflatable cuffs.…”
Section: Discussionmentioning
confidence: 99%
“…The manufacturer's guidelines state that the given inflation volumes (Table 1) are maximum values and lower values can suffice to obtain a seal and ⁄ or achieve the 60 cmH 2 O intracuff pressure [6]. Based on in vitro data, only a small fraction of the maximum recommended cuff filling volume was required to achieve a cuff pressure of 60 cmH 2 O [20]. Furthermore, even in the in vitro setting, the maximal recommended volumes result in hyperinflation of the cuff for almost all paediatric laryngeal mask airway brands and sizes [20].…”
Section: ó 2008 the Authorsmentioning
confidence: 99%
“…Based on in vitro data, only a small fraction of the maximum recommended cuff filling volume was required to achieve a cuff pressure of 60 cmH 2 O [20]. Furthermore, even in the in vitro setting, the maximal recommended volumes result in hyperinflation of the cuff for almost all paediatric laryngeal mask airway brands and sizes [20]. In vivo data are not yet available.…”
Section: ó 2008 the Authorsmentioning
confidence: 99%
“…It is also recommended in the instruction leaflet of many LMAs, but it has been shown that injecting this volume of air results in pressures > 60cmH 2 O. 17 Intubation does not always occur in theatre. Patients are often intubated during emergency situations either pre-hospital admission or in emergency departments.…”
Section: Discussionmentioning
confidence: 99%